تأثیر تمرینات باستخدام وسائل تدریبیة في الماء على بعض القدرات البدنیة وزمن انجاز سباحة 200 متر حرة للناشئین - خلود عبد الوهاب احمد (الرياضة المعاصرة)
The sport became the focus of any advanced society in the world because it is based on creating and building a generation of intellectual and physical potential. Therefore, developing countries devote all their efforts to the numbers of their members physically and Mharria and Khtttiya using the latest tools and training methods. So is the importance of research in the use of new style in sports training, namely resistance training with water, one of the modern methods for improving the physical and performance skills and achieve the feat 200m freestyle to come out with positive results. As research objectives level are preparing a training curriculum by opponents in the water and get to know the impact of the curriculum in some physical abilities and level of achievement of 200 m